Students’ understanding of evidence in science through studying paradoxes and the principle of falsification - Lockwood, Steven C. (Curtin University, 2014)
This thesis explores how students can come to understand the relationships between evidence, theory and logic within the field of science. I develop the role of the study of paradox as a teaching practice. I seek to ascertain the role that this type of study offers the development of students’ evidentiary logic and I question whether studying paradoxes can enhance students’ capacity to articulate their understandings.